2022
DOI: 10.22363/2687-0088-30084
|View full text |Cite
|
Sign up to set email alerts
|

Word frequency and text complexity: an eye-tracking study of young Russian readers

Abstract: Although word frequency is often associated with the cognitive load on the reader and is widely used for automated text complexity assessment, to date, no eye-tracking data have been obtained on the effectiveness of this parameter for text complexity prediction for the Russian primary school readers. Besides, the optimal ways for taking into account the frequency of individual words to assess an entire text complexity have not yet been precisely determined. This article aims to fill these gaps. The study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Sporadic eye-movement studies of reading in Russian children confirmed that word length and frequency influenced eye movements during reading and that the magnitude of these effects decreased with age (Alexeeva et al, 2020 for grades 3-4;Ivanov et al, 2010 for grades 1 and 4; Korneev et al, 2017;2018 for grades 2-3;Laposhina et al, 2022 for grades 1-3). Bezrukikh et al (2017) showed that the number of fixations and fixation durations, as well as saccades amplitudes, were related not only to the age of children (8-10 years old) but also to text complexity.…”
Section: Eye Movements During Reading In Russianmentioning
confidence: 96%
“…Sporadic eye-movement studies of reading in Russian children confirmed that word length and frequency influenced eye movements during reading and that the magnitude of these effects decreased with age (Alexeeva et al, 2020 for grades 3-4;Ivanov et al, 2010 for grades 1 and 4; Korneev et al, 2017;2018 for grades 2-3;Laposhina et al, 2022 for grades 1-3). Bezrukikh et al (2017) showed that the number of fixations and fixation durations, as well as saccades amplitudes, were related not only to the age of children (8-10 years old) but also to text complexity.…”
Section: Eye Movements During Reading In Russianmentioning
confidence: 96%
“…For text, factors such as complexity, readability, word frequency, and non-literalness can influence the information load [42,43]. For images, perceptual complexity, visual complexity, and visual features might dictate the information load [44][45][46].…”
Section: Information Overload and Underload In Hybrid Content Elementsmentioning
confidence: 99%
“…Previous research has yielded mixed results regarding the impact of product type on the helpfulness of online reviews. Some suggest the greater helpfulness of reviews for experience products due to their ability to mitigate uncertainty [12], while others argue for the supremacy of search products in this context, citing their reliance on objective information [42,43]. In light of the unique needs of experience products, we propose the following revised hypotheses: Hypothesis 3a (H3a).…”
Section: Product Typesmentioning
confidence: 99%
“…It is commonly assumed that a high rate of low-frequency words increases text complexity. The assumption has been proved by recent cutting-edge research (Laposhina et al, 2022). Second, despite their reference to specific real objects, terms lean towards conceptual abstraction (Tatarinov, 2006: 231-234).…”
Section: Introductionmentioning
confidence: 99%